Rancangan Crossover Dalam Penelitian Bidang Ergonomi - Tunas, I Ketut (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2022)
Crossover is one of the research designs, which provides a sequence of interventions for each research subject. In giving the intervention, the subjects were divided into two or more groups in period I, then the intervention was exchanged in the next period. Each individual gets all interventions in the research process. The purpose of this paper is to provide an overview of the crossover design in ergonomics research, especially the design, number of samples, period effects, carryover effects and statistical tests. Crossover design has a special design, which is a special design of controlled double blind randomized trial design. The number of samples in this crossover design is less than the parallel design. The existence of a period effect and carryover effect, then the statistical test used adjusts to the effect of the period and the carryover effect.